The feminist struggle in performing arts in Brazil - Romano, Lúcia R. V. [UNESP] (Taylor & Francis, 2021)
This article summarizes recent transformations in the field of performing arts in Brazil, with attention to feminist theatrical production. It provides a description of the context of this branch of Brazilian political theatre, between the civil-military coup of 1964 and the present, focusing on 2015, a period named the Brazilian 'Feminist Spring'. This historical arc of almost sixty years celebrates groups and artists which represent the dissemination of feminist discussion and poetics in all kinds of performative events in the theatrical field, as well as revealing the backlash represented by the anti-feminist policies of the Bolsonaro government, elected in late 2018.